PICTURES FOR IMPROVING INDONESIAN EFL STUDENTS’ SPEAKING COMPETENCE - Muhammad Aprianto Budie Nugroho (University of Kuningan, 2014)
Abstract: The purpose of this study is to investigate whether to what extent pictures can improve students’ speaking competence. It was carried out at SMAN in Cigugur for three months. The subject of the research was the students of SMAN in Cigugur in the academic year 2012/2013. The research method was classroom research and it was conducted in two cycles. The data was collected through interview, observation, diaries, document and test. The qualitative data were analyzed by using constant comparative method. While the quantitative data were analyzed by descriptive statistic to calculate the mean scores of pre-test, test, and post-test. The research findings show pictures can improve the students’ speaking competence by indicating their speaking fluency, appropriate vocabularies, grammatical sentences, and good pronunciation. The advantages of pictures were also shown by the classroom situation, i.e.: during the speaking class the students can answer teacher’s questions; the students had courage to express their idea freely; the speaking activities was not limited in the written way; and their attention in speaking class.Keywords: Speaking, pictures, students’ competence